Modeling the Impact of Metallic Ion Layers on Equatorial Spread F With SAMI3/ESF. Issue 5 (26th February 2020) - Huba, J. D.; Krall, J.; Drob, D.
Abstract: The impact of E region metal ion layers on the development of equatorial plasma bubbles is investigated using the SAMI3/ESF model. We find that metal ion layers reduce the growth rate of the generalized Rayleigh‐Taylor instability (GRTI) and act to suppress the development of equatorial plasma bubbles. This is consistent with theoretical expectations and observations and is attributed to the increase in both the Pedersen and Hall conductances. Additionally, inhomogeneities in the E region metal ion layer can map into the F layer and alter the morphology of equatorial spread F (ESF) bubble evolution. Lastly, we find that if EFS bubbles develop in the presence of a metal ion layer, then the electric fields generated by the instability can lift the metal ions into the F region. This is consistent with observations of Fe + in the F region during equatorial spread F . Key Points: Metal ion layers in the E region reduce the growth rate of the generalized Rayleigh‐Taylor instability Equatorial spread F can be suppressed for sufficiently dense E region metal ions If ESF does develop in the presence of metal ions, these ions can be lifted from the E region into the F region